2013
DOI: 10.4269/ajtmh.12-0378
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Aedes aegypti Population Dynamics in Field Systems: Quantifying Direct and Delayed Density Dependence

Abstract: Abstract. Transgenic strains of Aedes aegypti have been engineered to help control transmission of dengue virus. Although resources have been invested in developing the strains, we lack data on the ecology of mosquitoes that could impact the success of this approach. Although studies of intra-specific competition have been conducted using Ae. aegypti larvae, none of these studies examine mixed age cohorts at densities that occur in the field, with natural nutrient levels. Experiments were conducted in Mexico t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 37 publications
5
54
0
Order By: Relevance
“…However, several studies have expressed concern that a density-dependent increase in mosquito fitness may impede population suppression strategies [15, 18]. Our model predicts that increasing density-independent mortality reduces adult numbers despite alleviating the effects of competition on mosquito fitness, and therefore suggests that interventions to suppress populations by killing juveniles and adults are likely to be helpful.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, several studies have expressed concern that a density-dependent increase in mosquito fitness may impede population suppression strategies [15, 18]. Our model predicts that increasing density-independent mortality reduces adult numbers despite alleviating the effects of competition on mosquito fitness, and therefore suggests that interventions to suppress populations by killing juveniles and adults are likely to be helpful.…”
Section: Discussionmentioning
confidence: 75%
“…However, in A. aegypti , experimental studies have shown that fecundity, and juvenile survival and development rates, vary strongly depending on the level of larval density-dependent competition for food [1417]. Larval density-dependent demographic variation in field populations has proven difficult to quantify because mosquito populations have overlapping generations [15, 16, 18]. However, field observations of A. aegypti suggest that competition is often relatively intense.…”
Section: Introductionmentioning
confidence: 99%
“…; Walsh et al . ). A. aegypti rely on human blood to reproduce, and their larval habitat consists of water containers close to human dwellings, such as water storage jars and pot plant plates (Southwood et al .…”
Section: Introductionmentioning
confidence: 97%
“…Given the public health significance of these mosquitoes and the potentially large impact that density dependence could have on the success of mosquito control measures, surprisingly little is known about density dependence in these species under natural conditions. Although laboratory studies have provided insight into temperature and resource dependent growth and development of immature mosquitoes (Gilpin and McCleland 1979, Rueda et al 1990, Arrivillaga et al 2004), translating these into descriptions of natural environments is challenging (Walsh et al 2013). For instance, it is unclear how levels of nutrients used in lab experiments compare to those present in reality, or how development of immatures differs between constant and variable temperature settings.…”
Section: Introductionmentioning
confidence: 99%
“…the nature of food being consumed and the feeding habits of larvae) and in terms of its outcome (e.g. a description of how larval survival and/or development depends on the number of larvae present) (Walsh et al 2013). Dynamics of immature stages of Ae.…”
Section: Introductionmentioning
confidence: 99%